The impact of Diabetes Mellitus on Lower urinary tract symptoms (LUTS) in both male and female patients - Papaefstathiou, Efstathios; Moysidis, Kyriakos; Sarafis, Pavlos; Ioannidis, Evaggelos; Hatzimouratidis, Konstantinos (My University, 2019)
Introduction Contemporary studies examine the connection of Diabetes Mellitus (DM) with Lower urinary tract symptoms (LUTS), alone or associated with other factors of the metabolic syndrome. However, little research has occurred concerning patients with diabetes of both genders and sexes without other diseases of the lower urinary tract. The aim of this study is to examine the relationship between DM and LUTS. Methods The study enrolled 110 patients with DM and 134 healthy individuals. The IPSS questionnaire was used for the evaluation of symptoms from lower urinary tract. Data was analyzed with univariate and multivariate logistic regression using SPSS v.24. Results Analysis with moderate/severe LUTS as dependent variable and plausible confounding factors (age group, BMI, hypertension, dyslipidemia, years with DM and reported HbA1c) as covariates revealed that only HbA1c levels correlated independently with the presence of moderate/severe LUTS (p = 0,024, OR:2,729, CI:1,144–6,509) in diabetic women, while there was no statistically significant difference between male groups. HbA1c levels' correlation with IPSS-voiding and IPSS- storage score was not statistically significant. Quality of life is also affected in women with diabetes mellitus (p: 0,02). Conclusion Only an increase in HbA1c was independently connected with a deterioration of LUTS in the female group.
Keywords: Diabetes Mellitus; IPSS; Lower Urinary Tract Symptoms (LUTS)